Penance in medieval Europe, 600-1200 - Meens, Rob 1959- (Cambridge University Press, 2014)
Penance has traditionally been viewed exclusively as the domain of church history but penance and confession also had important social functions in medieval society. In this book, Rob Meens comprehensively reassesses the evidence from late antiquity to the thirteenth century, employing a broad range of sources, including letters, documentation of saints' lives, visions, liturgical texts, monastic rules and conciliar legislation from across Europe. Recent discoveries have unearthed fascinating new evidence, established new relationships between key texts and given more attention to the manuscripts in which penitential books are found. Many of these discoveries and new approaches are revealed here for the first time to a general audience. Providing a full and up-to-date overview of penitential literature during the period, Meens sets the rituals of penance and confession in their social contexts, providing the first introduction to this fundamental feature of medieval religion and society for more than fifty years
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 600-1200; Geschichte; Kirchengeschichte; Penance / History / Europe; Buße; Europa; Europe / Church history / 600-1500